Technological Resources to Enhance Orality in English (Docentes 2.0 Journal, 2026)
Oral proficiency in English is a fundamental skill in students' linguistic development and is one of the primary challenges in teaching English as a foreign language. The objective of this research was to conduct a systematic review of recent scientific literature on the use of technological resources to improve oral English expression in educational contexts. The study was framed within the interpretive paradigm, employing a systematic method, a qualitative approach, a thematic-narrative design, a documentary-bibliographic-analytical nature, and a cross-sectional scope. Information research was conducted across the Scopus, SciELO, and Web of Science databases, following the PRISMA guidelines. Initially, 128 scientific articles related to the topic were identified; after applying inclusion and exclusion criteria, a final corpus of 20 studies published between 2020 and 2025 was selected. The information was systematized using a documentary analysis matrix, which facilitated the recording of variables such as publication year, language, methodological design, and the main contributions of the analyzed studies. The analysis enabled the identification of research trends, the characterization of the documentary corpus, and the interpretation of findings reported in the literature. The results reveal a growing trend in scientific output on the use of educational technologies to develop oral English expression. Furthermore, it was observed that active methodologies mediated by digital resources foster student participation and contribute to the development of fluency, confidence, and autonomy in oral communication.
Keywords: Technological resources; oral expression; oral skill; didactic English